Maqashid Sharia Concerning Sexual Violence Against Wife In Law Number 23 Year 2004 - Nisa, Sayidah Khoirun; Ruslandi, Ruslandi (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2022)
This paper departs from the internal concept, namely the contract in marriage to form a man and a woman into a new family based on consensual relationships so that the purpose of marriage is to make them both Sakinah, mawaddah, warahmah. There are rights and obligations after the contract process including rights and obligations in fulfilling sexual needs between husband and wife, but in fact in the name of religion becomes the only basis if there is coercion from one of the parties who commits sexual coercion of a husband against his wife, which should be in a husband and wife relationship in a good way (ma'ruf) and cause mutual affection between the two. Based on the facts (reality) of the incident, the author discusses how Maqashid Syar'iah from acts of sexual violence against wives in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. By using normative juridical methods, in this case researching about sexual violence against wives according to Fiqh Munakahat and its relationship with Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT). The results of the study explain that to achieve and maintain 5 (five) main principles in Islam, namely maintaining religion (hifdz al-din), soul (hifdz al-nafs), reason (hifdz al-'qal), offspring (hifdz al-Nasl), and property (hifdz al-mal wa al-'irdh) then the victim must be protected and given justice, so that sexual violence does not happen again to a wife. Keywords: Maqashid Syari’ah; Violence; Sexual Violence.